Difusi Inovasi Metode Pembayaran Quick Response Code Indonesian Standard oleh Bank BPD Bali - I Gst. Ngr. Agung Krisna Aditya (Jurnal Multidisiplin Madani, 2022)
Efforts to diffuse the innovation of the quick response Indonesian standard (QRIS) payment method by Bank BPD Bali as one of the BUMD Banks in Bali Province. The Diffusion Theory of Innovation from Everett M. Rogers provides a novelty of theoretical analysis, especially the Sociology of Communication. The research was conducted using structured interviews, non-participatory documentation and documentation. Research conducted from November 2021 to July 2022 resulted in the findings of the QRIS innovation diffusion process adjusting to customer acceptance, characteristics of merchants and the heterogeneous community in Bali Province. The process of diffusion of innovation starts from the needs, experience and knowledge considering the advantages and disadvantages in determining decisions. The decision to choose or not to use QRIS is determined by the confirmation of the decision considerations. The differences in QRIS adopters are divided into innovators, early adopters, early majority, late majority and laggards.